ANALYZING THE EFFECT OF CUSTOMER EXPERIENCE AND BRAND IMAGE ON CUSTOMER SATISACTION OF KFC MANADO TOWN SQUARE - Tenda, Vinny Vennesya; Saerang, David P.E; Tielung, Maria V.J (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract: Customer satisfaction is the feeling of pleasure or disappointment incurred for comparing the performance of the products with the desire to be expected. If the performance of the product is lower as expected, then the customer will feel disappointed. It is important for a company to meet customer satisfaction. The aims of this study are to analyze the effects of customer experience and brand image on customer satisfaction withdrawing taking fast food restaurant KFC Manado Town Square as its case study. This research is causal type of research which uses primary data obtained through questionnaires and uses Multiple Regression Analysis. The population observed is people in Manado who have experienced bought the product and experience the facilities at the KFC Manado Town Square with 100 respondents as the sample size. The result of this study shows that customer experience and brand image have significant effects on customer satisfaction. It is important to provide good experience to customer in order to meet customer expectation. Consistent food quality, service quality and atmospheric quality increase customer satisfaction. KFC also has to keep building and maintaining the value of reputation of brand name. Keywords: fast food, customer experience, brand image, customer satisfaction